The most abundant nascent poly(A)+ RNAs are transcribed by RNA polymerase III in murine tumor cells - Kramerov, D.A.; Tillib, S.V.; Shumyatsky, G.P.; Georgiev, G.P. (Nucleic acids research, 1990)
Twelve to twenty percent of newly synthesized poly(A) + RNA is transcribed by RNA polymerase III in Ehrlich ascites carcinoma and P3O1 plasmocytoma mouse tumors. Most of this RNA designated as pol IIIpoly(A) + RNA has a size of 160 to 800 nucleotides with a maximum of distribution of ca. 300 nucleotides. Pol IIIpoly(A) + RNA fraction consists of two major classes of molecules corresponding to previously described B1 RNA and B2 RNA with the ratio of 1:4 to 2:3. All B2 RNAs present in poly(A) + fraction contain a long poly(A) segments at the 3' ends. Thus, RNA polymerase III transcripts can be polyadenylated. Several transcripts that hybridize with B2 probe were also observed in poly(A)- RNA. The major components consist of 180, 160, 120 and 95 nucleotides. The 180-nucleotide B2 RNA seems to be a primary transcript from B2 repeat. We suggest that other B2 RNAs are transcribed from truncated copies of B2 element.